CHANGES AND PROBLEMS IN THE ACTIVITIES OF WOMEN IN UZBEKISTAN IN THE 70-80S OF THE 20TH CENTURY - Boltayeva Gulnoza Rakhmatullayevna (Journal of Learning on History and Social Sciences, 2024)
In this article, the role of Uzbek women in social life, their production activities, changes and problems in their lifestyle in the 70s and 80s of the 20th century are analyzed in detail.